Exosomal miR‐95‐5p regulates chondrogenesis and cartilage degradation via histone deacetylase 2/8. Issue 11 (31st July 2018) - Mao, Guping; Hu, Shu; Zhang, Ziji; Wu, Peihui; Zhao, Xiaoyi; Lin, Ruifu; Liao, Weiming; Kang, Yan
Abstract: MicroRNAs play critical roles in the pathogenesis of osteoarthritis, the most common chronic degenerative joint disease. Exosomes derived from miR‐95‐5p‐overexpressing primary chondrocytes (AC‐miR‐95‐5p) may be effective in treating osteoarthritis. Increased expression of HDAC2/8 occurs in the tissues and chondrocyte‐secreted exosomes of patients with osteoarthritis and mediates cartilage‐specific gene expression in chondrocytes. We have been suggested that exosomes derived from AC‐miR‐95‐5p (AC‐miR‐95‐5p‐Exos) would enhance chondrogenesis and prevent the development of osteoarthritis by directly targeting HDAC2/8. Our in vitro experiments showed that miR‐95‐5p expression was significantly lower in osteoarthritic chondrocyte‐secreted exosomes than in normal cartilage. Treatment with AC‐miR‐95‐5p‐Exos promoted cartilage development and cartilage matrix expression in mesenchymal stem cells induced to undergo chondrogenesis and chondrocytes, respectively. In contrast, co‐culture with exosomes derived from chondrocytes transfected with an antisense inhibitor of miR‐95‐5p (AC‐anti‐miR‐95‐5p‐Exos) prevented chondrogenic differentiation and reduced cartilage matrix synthesis by enhancing the expression of HDAC2/8. MiR‐95‐5p suppressed the activity of reporter constructs containing the 3ʹ‐untranslated region of HDAC2/8, inhibited HDAC2/8 expression and promoted cartilage matrix expression. Our results suggest that AC‐miR‐95‐5p‐Exos regulate cartilage development and homoeostasis by directly targeting HDAC2/8. Thus, AC‐miR‐95‐5p‐Exos may act as an HDAC2/8 inhibitor and exhibit potential as a disease‐modifying osteoarthritis drug.